COLOUR REVOLUTIONS AND PARLIAMENTARIANISM IN THE CONTEXT OF DEMOCRATIZATION ON POST-SOVIET SPACE - A. M. Akmatalieva (Сравнительная политика)
Main approaches to the studies of internal and external causes of colour revolutions in Georgia, Kyrgyzstan and the Ukraine are reviewed. The article considers colour revolutions in the context of the fourth wave of democratization and concludes that colour revolutions encouraged the development of the civil society, party systems, parliamentarianism, the transparency of state bodies, and electoral process.